Evaluation of newborn screening in the state of Mato Grosso from 2005 to 2019 - Roseli Divino Costa; Maria de Fátima de Carvalho Ferreira; Thaís de Almeida Rocha; Marcial Francis Galera (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To evaluate quality indicators of the Neonatal Screening Referral Service of the state of Mato Grosso (NSRS-MT) from 2005 to 2019. Methods: Cross-sectional, retrospective, exploratory, descriptive, and observational study from 2005 to 2019. The following parameters were analyzed: age of newborns at the first collection, time between sample collection and arrival at the laboratory, time between the arrival and release of results and time between requesting the second sample and arrival at the NSRS. The population coverage of the program and the incidence of each clinical situation screened were also analyzed. Results: NSRS-MT coverage was analyzed and recorded as 76%. The incidence was analyzed for congenital hypothyroidism (CH) 1:1867, phenylketonuria (PKU) 1:33,311, sickle cell disease (SCD) 1:2004, cystic fibrosis (CF) 1:12,663, congenital adrenal hyperplasia (CAH) 1:15,843, and biotinidase deficiency (DB) 1:25,349. The median age (days) at the first consultation was: 44 for HC, 22 for PKU, 60 for DF, 52 for FC, 79 for HAC and 79 for DB. The mean time between exam collection and delivery to the NSRS was 8.4 days; between the arrival and release of results, 9 days; and for the return of recalls, 59 days. Conclusions: Regarding the coverage of the target population and collection at the ideal age, the NSRS-MT presents values below the national average. However, regarding the mean age at the time of the first consultation, the state's performance is better than the national.